Detection of immunoglobulin M antibodies with antigen-tagged latex particles in an immunosorbent assay. - Remington, J S (1983)
A method is described for the detection of immunoglobulin M (IgM) antibodies to Toxoplasma gondii by using latex particles coated with antigens of the organism. An excellent qualitative agreement was noted when the latex method was compared with other tests for the detection of IgM toxoplasma antibodies. The method is simple and inexpensive to perform and does not require the use of whole killed organisms or an enzyme conjugate.